Poverty alleviation and natural resources management in Madagascar : some findings on ecotourismTT - - Sarrasin, Bruno (1968-....) (Université des Antilles et de la Guyane (1982-2015), 2011)
The process of globalization, which has accelerated over the last twenty years, has raised important development issues, on the one hand, economic issues; on the other hand, globalization has also raised important social problems; the problems are also environmental, due to the increased needs and resource limitations. Tourism represents the ideal vector of this globalization and the issues it represents. This article seeks to better understand the challenges of the development of international tourism resources, by seeking an answer to the question: How ecotourism can constitute a real economic development strategy, fighting poverty and contributing to economic growth and the protection of natural resources?